Aquisição de densidade mineral óssea e prática de modalidades esportivas de combate em jovens - Ito, Igor Hideki [UNESP] (2015)
Objective: To analyze, over a cohort of 09 months of follow up, the bone mass gain is higher among young people involved in different sports Combat (MEC) compared to the control group (CG). Methods: In the study the basic measures, the MEC Group Inclusion criteria were: (i) aged 11 and 17 (ii) a minimum of 06 months of practice and (iii) the permission of the coach or teacher in charge to participate. In all, 50 adolescents of both sexes (19 girls and 31 boys) who were involved in MEC and met the inclusion criteria were selected sports clubs in different areas of the city: Karate (09 girls and 05 boys [Shotokan style]), judo (08 girls and 10 boys) and Kung-fu (02 girls and 16 boys [sanda style]). On the other hand, the inclusion criteria for the control group (CG) were: (i) aged between 11 and 17 and (ii) not engaged in regular physical activity / sport outside school. In the baseline measurements, this group was composed of 90 adolescents from schools and non-profit associations from different regions of the city (36 girls and 54 boys) who also composed convenience sample. Thus, the start of the sample cohort was composed of 140 adolescents, mean age 12.6 years, of both sexes. After the following 09 months, 140 young people initially evaluated, 67 individuals were assessed and included in this document, including 11 boys and 06 girls CG (n = 17) and 31 boys and 19 girls of the MEC Group (n = 50). The evaluation of BMD was performed by DEXA, the whole body and then analyzed the DEXA program separated in different regions of the body: (i) the total BMD, (ii) BMD of the lower limbs, (iii) BMD of the upper and ( iv) BMD of the spine vertebra. Results: Comparison of BMD between different MEC groups and the control group showed statistically significant differences for all body regions analyzed except the pelvis (p-value = 0.966). To lower limbs higher values were found in the initial period (CG = 1.061 ± 0.028 and 1.146 ± 0.015 = MEC) and ...